MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI AK2 DI SMK PELITA GEDONGTATAAN - Qurni, Wais Al; Gusliana, Evi; Sari, Ruly Nadian (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2018)
In general Islamic Religious Education is a subject developed from the basic teachings contained in Islam. So the lessons of Islamic Religious Education not only deliver the students to master the various teachings of Islam. But the important thing is how learners can practice those teachings in everyday life. Management learning Islamic Religious Education is an attempt by teachers in managing learning so that learning can improve students' learning motivation. Therefore, learning management is very important in a teaching and learning activities.motivation Learning in SMK Pelita Gedongtataan. This research uses qualitative research. Data collection was done through observation method, interview / interview, and documentation, questionnaire. The informants were the Headmaster, Waka Curriculum, and PAI Teachers as well as the AKI Class XI. Meanwhile, to analyze the data using qualitative descriptive analysis technique, that is to describe and interpret the data that has been in can so describe the actual reality in accordance with the existing phenomenon. Result of research indicate that planning of learning of PAI in SMK Pelita Gedongtataan is PAI teacher to make learning plan according to the material that will be submitted, implementation of learning of PAI in SMK Pelita Gedongtataan in accordance with what has been planned by PAI teacher that exist, and teacher of PAI also use some how to improve the motivation of learners in following the learning activities, evaluation of learning PAI in SMK Pelita Gedongtataan goal is to know the extent to which students can understand the material and also can improve the learning motivation learners so that the results obtained in accordance with what is expected. Result of research from learning management of PAI in improving student's motivation of class XI AK2 SMK Pelita Gedongtataan is good enough, although still far from level of perfection.